Experimental evaluation of sensor readings in invasive electrical capacitance tomography for conducting pipe applications—initial study - Haziq Syakir, Hamzah; Yasmin, Abdul Wahab; Ain Eazriena, Che Man; Nurhafizah, Abu Talip Yusof; Mohd Mawardi, Saari (Springer International Publishing, 2024)
Electrical Capacitance Tomography (ECT) is a promising imaging technique for monitoring gas–liquid flows in industrial pipelines. In this study, we developed an ECT system with eight electrodes to detect the presence of static gas inside oil, specifically for oil–gas regime. We optimized the sensor design using a Design of Experiment (DOE) method and developed a signal generator and signal conditioning system to collect data offline. Our experimental approach involved the use of an invasive approach with the placement of sensors within the pipe to improve the accuracy of the measurements. We conducted a series of experiments with different oil–gas regimes to evaluate the performance of the ECT system. The results demonstrate that the invasive approach significantly enhances the sensor readings, leading to improved imaging accuracy and reliability for detecting static gas inside oil. This study contributes to the understanding of the sensor reading performance in invasive ECT for oil–gas regime and provides valuable insights for optimizing the measurement process. The findings have implications for the development of more robust and accurate ECT systems in industrial settings.